PERAN PEMERINTAH TERHADAP PENINGKATAN EKONOMI PADA DESTINASI WISATA SUNGAI KUPAH BERBASIS MASYARAKAT DESA KABUPATEN KUBU RAYA - NIM. A1012191192, CITRA ADITAMA (Fakultas Hukum Universitas Tanjungpura, 2024)
Abstrac Sungai Kupah Village is one of the villages in Sungai Kakap District, Kubu Raya Regency. Sungai Kupah Tourism Destination is one of the tourist destinations not far from the center of Pontianak City and is one of the destinations that is often visited by tourists. The objectives to be achieved in this study are to obtain information about the role of the government in developing the potential of Sungai Kupah Tourism Village in Kubu Raya Regency. And to obtain information about the role of the government in improving the community's economy through the tourism industry.This research uses empirical legal research methods based on the gap between existing legal norms and their implementation in society. Based on the problems studied by the author, the author uses empirical legal research methods. Empirical legal research is carried out by researching directly into the field to see firsthand the application of legislation or rules of law relating to law enforcement, as well as conducting interviews with several respondents who areconsidered to be able to provide information regarding the implementation of law enforcement.The results of this research explain that according to Law Number 10 of 2009 concerning Tourism, the Government's role in the Kupah River tourist destination has not been implemented according to this Law. That the Kupah River tourist destination still has many shortcomings from the development stage and the people in the tourist destination area have not been able to utilize the Kupah River tourist destination as a source of income to the maximum. That the Kubu Raya Regency Government has not optimally carried out its obligations to build physical and non-physical facilities in the Kupah River community tourism area, and has not made efforts to increase cleanliness and economic income at the Kupah River Tourism Destination.Keywords: Role, Government, Sungai Kupah, Destination, Tourism Abstrak Desa Sungai Kupah merupakan satu diantara desa yang berada di Kecamatan Sungai Kakap, Kabupaten Kubu Raya. Destinasi Wisata Sungai Kupah merupakan salah satu destinasi wisata yang tidak jauh dari pusat Kota Pontianak dan menjadi salah satu destinasi yang sering dikunjungi wisatawan. Tujuan yang ingin dicapai dalam penelitian ini adalah untuk mendapatkan informasi mengenai peran pemerintah dalam mengembangkan potensi Desa Wisata Sungai Kupah di Kabupaten Kubu Raya. Dan untuk mendapatkan informasi mengenai peran pemerintah dalam meningkatkan ekonomi masyarakat melalui industri pariwisata.Penelitian ini menggunakan Metode penelitian hukum empiris berpijak dari adanya kesenjangan antara norma hukum yang ada dengan pelaksanaannya dalam masyarakat. Berdasarkan permasalahan yang diteliti oleh penulis maka penulis menggunakan metode penelitian hukum empiris. Penelitian hukum empiris dilakukan dengan meneliti secara langsung ke lapangan untuk melihat secara langsung penerapan perundang-undangan atau aturan hukum yang berkaitan dengan penegakan hukum, serta melakukan wawancara dengan beberapa responden yang dianggap dapat memberikan informasi mengenai pelaksanaan penegakan hukum tersebut.Hasil penelitian ini menjelaskan bahwa Destinasi Wisata Sungai Kupah Bahwa menurut Undang